Function of cultural schemata in written discourse by Korean as foreign language learners in Malaysia - Lee, Ji Soo; Abd Rahim, Normaliza (Penerbit UTM Press, 2017)
With globalization, the growing development of Internet has increased each cultural area. Since the 2000s, the Korean cultural wave (Hallyu) has boomed up in East Asia and an increasing number of young people have enrolled in Korean language courses. With the increased access to the language, it has been noted that specific expressions in certain contexts could be interpreted differently by learners from other cultures. This can be problematic when such learners rely only on their linguistic skills to communicate with foreign interlocutors due to different points of view in multicultural societies. In the field of cross cultural pragmatics, several researchers analyzed the discourses among interlocutors from different cultures and have highlighted the importance of cultural schemata in multicultural and multilingual societies. This paper considers how culture influences communication in cross cultural pragmatics by investigating written discourses of Malaysian learners of Korean language as Foreign Language. It expounds upon how most difficulties, misunderstandings, and break offs in communication stem from differences among interlocutors with different cultural backgrounds.